Characteristic alterations of long-loop "reflexes" in patients with Friedreich's disease and late atrophy of the cerebellar anterior lobe. Issue 7 (July 1984) - Diener, H C; Dichgans, J; Bacher, M; Guschlbauer, B
Abstract : Sudden tilting of a platform around the axis of the human ankle joint causes a regular pattern of short and medium latency EMG responses in the stretched triceps surae muscle and a long latency response in its antagonist, the anterior tibial muscle. This paper reports alterations of these EMG responses in 41 patients with cerebellar lesions. Patients with anterior lobe atrophy exhibited normal latencies of all EMG responses, but an increase in duration and amplitude of the long latency response. This may at least partially explain the 3 Hz postural tremor, which can be evoked in these patients through a toe-up tilt of the platform. Patients with lesions restricted to the vestibulocerebellum and to the cerebellar hemispheres exhibited normal latencies of all EMG responses. The most specific finding in all of the patients suffering from Friedreich's ataxia (affecting spinal afferents) was the massive delay of the stabilising response of the anterior tibial muscle. The fact that the patients with lesions restricted to the cerebellum invariably exhibited normal latencies of postural "reflexes" indicates that the exact "timing" of these responses is independent of the cerebellum. The duration and amplitude of the long latency response of the antagonist, however, seems to be controlled by the cerebellum.